Characteristics of streaky thermal footprints on wind waves - Lu, Guan-hung; Tsai, Wu-ting; Garbe, Christoph S.; Jähne, Bernd (Journal of geophysical research. Oceans, 2021)
Coherent vortices in the aqueous surface layer beneath wind waves manifest themselves by inducing elongated high-speed streaks on the interface. Analyses of thermal images taken in the wind-wave flume reveal that the mean streak spacing scaled by the viscous length, , depends strongly on the wind-wave condition. This contradicts the wall-bounded turbulent flow in which the scaled mean streak spacing approaches a canonical value, . Comparative numerical simulations of shear flow bounded by flat and wavy surfaces are conducted to explain the variation. In the low-wind range with insignificant surface waves, ; the reduction of is attributed to the insufficient shear rate to form the elongated streaks. For the moderate-wind range in which surface waves become pronounced but remain to be unbroken, is still less than 100. Analysis of the vorticity transport in the simulated wavy flows reveals that the presence of non-breaking waves enhances the formation of quasi-streamwise vortices and the surface streaks. For the high-wind range, surface waves break and the breakers wipe out the streaks. The streaks quickly reestablish in the wake of the breaker with mean spacing but are destructed again by the following breaker.
Gesehen am 04.09.2021